The simulation of physical mechanism for HTM-free perovskite organic lead iodide planar heterojunction solar cells. (25th August 2015) - Fu, Kailiang; Zhou, Qian; Chen, Yongsheng; Lu, Jingxiao; Yang, Shi-E
Abstract: Recently, organo-metal halide perovskites have attracted much attention from the scientific community because of their successful application in the absorber layer of low-cost solar cells. For the further improvement of the performance of such cells, a thorough understanding of the influence of the material properties on the working mechanism of a device is very necessary and important. In this study, two-dimensional modeling of hole transport material free planar heterojunction solar cells was performed, in which electromagnetic simulation was directly linked to carrier transport calculations. An optimum absorber thickness of 200 nm was reproduced in the simulation at carrier diffusion length of 100 nm, in good agreement with previous experiments. This optimum thickness increased with the increase of diffusion length, and an efficiency of about 11% was obtained at 300 nm with a diffusion length of 300 nm. Finally, it was demonstrated that the relatively low efficiency of such solar cells was directly related to the low short-circuit photocurrent density ( J SC ) and the low open-circuit voltage ( V OC ) due to the insufficient absorption of the long-wavelength region and the nearly intrinsic doping concentration, respectively.